PENGEMBANGAN OBJEK WISATA PANTAI PELAWAN BERBASIS AGILE GOVERNANCE DI KABUPATEN KARIMUN TAHUN 2023 - Zaki, Muhammad; Rafi, M. (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
Pelawan beach tourism is one of the favorite tourist attractions in Karimun Regency which has the uniqueness of a stretch of white sand and a charming blue sea so that Pelawan beach is very good to be developed. However, there is a phenomenon, namely the decreasing number of tourist visits, so that organizational governance is needed by the government in developing tourism potential and providing benefits quickly, namely the development of tourist attractions based on agile governance. This study aims to determine and describe the development of Pelawan beach tourism objects based on agile governance in Karimun Regency in 2023. This study uses a qualitative approach & descriptive research type. The data used are primary data obtained from research informants and supported by secondary data obtained from official government documents and scientific publications. Data collection techniques in this study are by interview and documentation.The results of the study indicate that the development of Pelawan beach tourism objects based on agile governance has not been fully maximized because there are indicators of agile governance that have not been met, such as the lack of new innovations and an adaptive approach to changes that occur by the Karimun Regency Tourism Office. In addition, several obstacles that occur such as budget limitations and low tourism awareness by the local community are challenges for the Karimun Regency Tourism Office in developing Pelawan beach tourism objects based on agile governance in Karimun Regency in 2023. Keywords: Agile Governance, Tourism Objects, Tourism Object Development